PENGARUH DANA PIHAK KETIGA, CAPITAL ADEQUACY RATIO, RETURN ON ASSETS , DAN NON PERFORMING LOAN TERHADAP PENYALURAN KREDIT PADA BPR KONVENSIONAL DI PROVINSI BALI TAHUN 2016 - Zulfa Maulida Rifki Fitria, 14.05.52.0243; N. Masdjojo, Gregorius (Students Journal of Accounting and Banking, 2018)
This research aims to analyze the factors that influence the distribution of credit on BPR Conventional of Bali quarter-IV (December 2016). The dependent variable in this research is the distribution of credit, while the independent variables in this research are DPK (third-party funds), CAR (Capital Adequacy Ratio), ROA (Return On Assets), dan NPL (Non Performing Loan). This type of research is a cross section, the data used are secondary data fromÂ  OJK that is the publication of the report BPR Conventional. The sampling technique used was purposive sampling so that from 137 BPR Conventional obtainable 130 BPR Conventional. A method of data analysis in this research using multiple linear regression analysis using OLS and processed with SPSS program 21. The results of this research show that the DPK and ROA positive and significantly against the distribution of credit. While the CAR negative effect and significantly against the distribution of credit, and the NPL negative effects and insignificant against the distribution of credit.Keywords: the distribution of credit, third-party Funds (DPK), Capital Adequacy Ratio (CAR), Return On Assets (ROA), Non Performing Loan (NPL).